2022
DOI: 10.3390/nu14020295
|View full text |Cite
|
Sign up to set email alerts
|

Front-of-Pack Labeling in Chile: Effects on Employment, Real Wages, and Firms’ Profits after Three Years of Its Implementation

Abstract: This study evaluates the impact of Chile’s innovative law on Food Labeling and Advertising, enacted in June 2016, on employment and real wages and profit margins for the food and beverage manufacturing sectors in the 2016–2019 period, using unique company-specific monthly data from Chile’s tax collection agency (measuring aggregate employment, real wages, average size of firms, and gross profit margins of the food and beverage manufacturing sector). Interrupted-time series analyses (ITSA) on administrative dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…When adding menu labelling was in play in California and in King County, Washington, the food industry raised concerns about implementation costs [ 37 , 38 ]. In the case of income and profits, there is no scientific evidence supporting this; on the contrary, an evaluation of the effects of Chile’s FOPL on employment, salaries and gross profits of companies showed that there was no effect on these variables [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…When adding menu labelling was in play in California and in King County, Washington, the food industry raised concerns about implementation costs [ 37 , 38 ]. In the case of income and profits, there is no scientific evidence supporting this; on the contrary, an evaluation of the effects of Chile’s FOPL on employment, salaries and gross profits of companies showed that there was no effect on these variables [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A well-designed warning label can help to combat obesity especially, and some studies suggest that on a daily basis, consumers are subjected to many messages about low-nutrient foods-particularly, close to the point of sale [48]. On the other hand, it has been already proven that labels including health warnings-especially those that include a combination of image and text-are likely to decrease the number of energy-dense snacks purchased online [10]. The analysis of the answers provided by the group of Polish respondents allowed us to conclude that they see the need to take action aimed at reducing the consumption of sweetened beverages.…”
Section: Discussionmentioning
confidence: 99%
“…In the last several years, sugar consumption has been a subject of public health-related debates aimed at answering the following question: how to efficiently decrease the intake of added/free sugar in society. Across the world, many strategies have been used, including sugar tax [6], nutritional claims, warning labels [7,8], or imposing limits on the TV and radio advertising of high-sugar products, especially prohibiting the marketing of high-sugar products to children [9,10]. Quite often, individual governments choose fiscal policy tools such as sugar tax as the first action aiming to decrease, e.g., purchasing sugar-sweetened beverages, which has also been recently recommended by the WHO.…”
Section: Introductionmentioning
confidence: 99%
“…The food industry, at that time, claimed that the law would lead to decreases in corporate income, and thus an adverse outlook on employment in Chile, and also claimed that the law would breach international trade agreements. However, these intimidation tactics did not work and their predictions did not materialize once the law was adopted (Paraje et al 2021(Paraje et al , 2022. Nevertheless, these arguments have continued to be used in other countries (Crosbie, Carriedo, and Schmidt 2022).…”
Section: Existing Public Policies Across the Globe And Of Potential U...mentioning
confidence: 99%